Jahwe - „szybki śwadek” w Ml 3,5b na tle literatury międzytestamentalnej i rabinicznej - Zawadzki, Arnold (The Biblical Annals, 2016)
The article analyzes the imagery of God as a “swift witness” (Mal 3:5b) against the backdrop of the Jewish biblical, intertestamental, and rabbinic traditions. By adopting the reference to the deuteronomistic institution of the witness which provided surety for the observance of the Sinaitic covenant, the prophet implicitly expresses the advent of a religious crisis signaled by the lack of proper religious identity and by the weakening of the temple institutions created to safeguard and cultivate this identity. The image of God as a “swift witness” who comes to his temple to execute judgment on those who break the Covenant, and to inaugurate the ultimate era of justice, constitutes the prophet’s answer to all those who harbor doubt about God’s justice.